A Study on Traditional and Modern Banking System: Exploring the impact of modern banking on financial transactions (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The majority of the country's network providers have embraced the new modern bankingsystem. The term modern banking refers to the practice of utilizing mobile phones for financialtransactions. Despite its youth, the internet has quickly developed into a fully developed medium. Peoplethroughout the world have easier access to the internet than to any other media (save television).Several businesses in Ghana are embracing e-marketing as a means of keeping up with global rivalsgiven that more individuals in the country have internet access than ever before. Because of the effortsof network providers, consumers may now use their mobile phones to get access to the web from justabout any place. The goals of this study include identifying when and where beneficiaries may get theirmoney, as well as what kinds of documents will be needed. The study revealed that clients must provideidentification and a PIN to withdraw funds. respondents also noted that they spend less timewithdrawing money thanks to modern banking.